An efficient mechanical metamaterial component with alternating Poisson's ratios and opposite orthogonal behaviors. (December 2022) - Zhang, Wei-Ming; Guo, Meng-Fu; Yang, Jin-Shui; Ma, Li
Abstract: In some extreme environments, mechanical metamaterials can be actuated by mechanical actuating instead of electronic controls to realize functions such as mechanical signal output, logic gate operations, or other self-decision functions. This paper proposes a three-dimensional mechanical metamaterial with alternating Poisson's ratios and opposite orthogonal behaviors (AOPR metamaterials). The alternating Poisson's ratios enable AOPRs to complete the alternating action under only one-time unidirectional actuating action. The orthogonal opposite behaviors enable AOPRs to simultaneously perform signal output in two directions and binary logic control. These two unique properties greatly enrich mechanical metamaterials' information expression ability and logical judgment ability. Using AOPRs as mechanical components can significantly reduce the temporal and spatial consumption required to complete logic operations or control functions. We expect to provide a mechanical component design strategy for helping mechanical computers and automatic controllers reduce the structural volume and improve the operational speed. Graphical Abstract: ga1